2009
DOI: 10.1097/wnn.0b013e318190d185
|View full text |Cite
|
Sign up to set email alerts
|

Speech Acquisition in Older Nonverbal Individuals With Autism

Abstract: Individuals with autism often fail to develop useful speech. If they have not done so by age 5, the prognosis for future development has been thought to be poor. However, some cases of later development of speech have been reported. To quantify and document the nature of later speech development and the factors that might be important for prognosis, we reviewed the extant literature. We searched both manually and electronically, examining all literature with at least an English-language abstract, through March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
2
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 64 publications
(82 reference statements)
2
66
2
9
Order By: Relevance
“…There have been, in addition, case reports of nonspeaking children acquiring language later (Pickett, Pullara, O'Grady, & Gordon, 2009), even in adolescence (Mirenda, 2003;Windsor, Doyle, & Siegel, 1994). In this section, assessment at the beginning of language acquisition, from the time at which the child begins using words as the primary form of communication to the point at which the child produces more or less complete sentences, will be addressed.…”
Section: Assessing Early Linguistic Communicationmentioning
confidence: 99%
“…There have been, in addition, case reports of nonspeaking children acquiring language later (Pickett, Pullara, O'Grady, & Gordon, 2009), even in adolescence (Mirenda, 2003;Windsor, Doyle, & Siegel, 1994). In this section, assessment at the beginning of language acquisition, from the time at which the child begins using words as the primary form of communication to the point at which the child produces more or less complete sentences, will be addressed.…”
Section: Assessing Early Linguistic Communicationmentioning
confidence: 99%
“…IQ during childhood and early language ability appeared to be the strongest predictors of adult outcome in this review. One other summative review reported on the outcomes of nonverbal individuals with ASD (Pickett, Pullara, O'Grady, & Gordon, 2009). This review identified 64 published materials that had reported a total of 167 children with ASD who had developed speech at or after the age of five.…”
Section: Introductionmentioning
confidence: 99%
“…Remaining nonverbal past the age of 5 years has been considered a poor prognostic indicator for future language development (Billstedt, Carina Gillberg, & Gillberg, 2007; Picket, Pullara, O'Grady, & Gordon, 2009). Although there have been reports of individuals older than 5 acquiring speech (e.g., Picket, et.…”
mentioning
confidence: 99%